EFFECT OF SELECTED YOGA TECHNIQUES ALONG WITH ASHWAGANDHA AND VACHA IN DEPRESSION IN THE AGE GROUP 65–75 YEARS - MELEPPURAKKAL, SOUMYA; V K, SUNITHA; D, JAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study was done to compare the effect of selected yoga techniques, drugs, and combined therapy in depression in geriatrics. Methods: 75 patients between 65 and 75 years of age with depression were included in the study which was assessed by HAM D Score. The study population was randomly allocated to one control group and two study groups. The control group was given Aswangandha and Vacha churna with warm water as anupana after food, selected yoga techniques in the first study group, and combined yoga and the drug were given to the second study group. Outcome variables were assessed for the groups after the 30th day and follow-up after 45 days. Results: The results obtained in the study were analyzed using the ANOVA test. Yoga along with drug experienced a comparatively greater reduction in HAM-D score after treatment and follow-up (p<0.05) than other groups. Conclusion: Holistic approach can bring a better and static result than applying the treatment modalities alone.